2020
DOI: 10.1021/acs.energyfuels.0c02525
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of Metals in Asphaltenes by High-Performance Thin-Layer Chromatography and Solid–Liquid Extraction Hyphenated with Elemental and Molecular Identification

Abstract: Asphaltenes are among the most challenging components in petroleum processing because they contain high amounts of heteroatoms (i.e., S, N, O, V, and Ni) thought to be responsible for strong aggregation tendencies, precipitation, and fouling problems. The role of vanadium and nickelcontaining petroleum compounds (i.e., "petroporphyrins") in aggregation and fouling is not completely understood because asphaltene composition and structure is still a subject of debate in the petroleum chemistry community. Charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…81 High-performance thin-layer chromatography. Moulian et al 82 studied the contribution of porphyrins to asphaltene aggregation and reported an increase in the molecular weight of asphaltene aggregates in the presence of metalloporphyrins that interacted with asphaltene aggregate surfaces, and these species likely play a critical role in asphaltene aggregation, coprecipitation, and demetallation processes. Importantly, this study directly implicates porphyrins in the stabilization of noncovalent asphaltene aggregates, consistent with simulations reported more than a decade previously.…”
Section: Selective Affinity Chromatographymentioning
confidence: 99%
See 3 more Smart Citations
“…81 High-performance thin-layer chromatography. Moulian et al 82 studied the contribution of porphyrins to asphaltene aggregation and reported an increase in the molecular weight of asphaltene aggregates in the presence of metalloporphyrins that interacted with asphaltene aggregate surfaces, and these species likely play a critical role in asphaltene aggregation, coprecipitation, and demetallation processes. Importantly, this study directly implicates porphyrins in the stabilization of noncovalent asphaltene aggregates, consistent with simulations reported more than a decade previously.…”
Section: Selective Affinity Chromatographymentioning
confidence: 99%
“…However, molecule-level characterization using MALDI FT-ICR MS revealed vanadyl porphyrins for only the TLC fraction eluted with acetone. 82 The combination of molecule-level (FT-ICR MS) and elemental analyses (ICP-MS) proved that abundant porphyrins are inaccessible to FT-ICR MS because of matrix effects and ionization efficiencies. 82 Importantly, these porphyrins are present in asphaltene fractions that contain abundant archipelago asphaltenes, which experience a disproportional aggregation tendency compared with island structural motifs.…”
Section: Selective Affinity Chromatographymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, there is no clear understanding of the role of porphyrins on asphaltene aggregation during the formation of asphaltene supramolecular aggregates. Thus, exploring the roles of porphyrins on the aggregation of asphaltenes is significant for researching the aggregation of asphaltenes and solving the problems caused by asphaltenes. …”
Section: Introductionmentioning
confidence: 99%